Analisis Integrasi Pasar Spasial Harga Daging Sapi di Provinsi Jambi - Bayu Krisna; Firmansyah Firmansyah; Fachroerrozi Hoesni (Universitas Batanghari, 2021)
This study aims to analyze the spatial market integration of beef prices in supporting the stabilization of prices for basic livestock products in Jambi Province. Spatial Market Integration Analysis Beef prices in Jambi Province use secondary data which is weekly time series data for the period 2018 – 2021 (August). The data analyzed in this study is the price of beef in the markets of Jambi City and Bungo Regency. The analytical method used to see the level of spatial integration of the beef market in supporting the stabilization of livestock staples both in the short and long term in Jambi Province is the VAR (Vector Autoregression) / VECM (Vector Error Correction Model) model. The study concludes that the weekly average beef price in Jambi City and Bungo Regency during the period 2018 to 2021 (August) is cointegrated. There is a long-term relationship between weekly average beef prices in Jambi City and Bungo Regency. The VECM model is more accurate in forecasting the weekly average beef price in Jambi City and Bungo Regency in the future.